Formulation and evaluation of papaya-flavored goat milk for expectant mothers - Fadzil, Adibatul Husna; Zulkifli, Norsakina Zurina; Salleh, Nunshaimah; Ali, Rosliza; Yaacob, Yanti; Md Rasid, Hamizah (2024)
This study aimed to reduce the gamey taste of goat milk and analyze its chemical composition after adding the papaya powder, using Fourier Transform Infrared Spectroscopy (FTIR). Goat milk from Suffy's Dairy Milk powdered milk and freeze-dried papaya powder had been used for the materials. FTIR analysis identified the functional groups present in the goat milk powder, papaya powder, and their new formulation. The spectra revealed that goat milk and papaya powder shared similar functional groups, including alcohols (O-H), alkanes (C-H), carbonyl (C=O), amines (N-H), and alcohols (C-O). In contrast, the new formulation goat milk papaya flavoured displayed a combination of the peak in papaya powder and goat milk powder. For the optimal formulation, a 4:6 ratio of goat milk to papaya powder was preferred. This ratio effectively reduced the gamey flavor and aroma of the goat milk, resulting in a more pleasant taste and a yellow-orange color. Additionally, the ideal temperature for dissolving the mixture was found to be 80°C.